Hubungan Bauran Pemasaran terhadap Loyalitas Pelanggan di Perusahaan DetailBOX Autodetailing Center - Muhammad Rifki; Mazaya Mazaya (Neolectura, 2022)
In business communication there are many tools in doing marketing, one of which is the Marketing Mix. The purpose of this study was to determine the relationship between the Marketing Mix and Customer Loyalty in the DetailBOX Autodetailing Center company. The increasing lifestyle of the Indonesian people who use cars and motorbikes as a means of transportation in their daily lives, and supported by the increasing number of vehicle sales every year, therefore people need a service for the maintenance of their vehicles. Respondents involved in this study were customers from DetailBOX which were taken as many as 125 respondents. By meeting the criteria for the sample, the respondents are customers who have used DetailBOX services continuously. The sampling technique used is non-probability sampling with the Convenience Sampling technique method. And the data is then processed using the SPSS version 25 program. The results of this study indicate that the Marketing Mix does not have a strong relationship with Customer Loyalty because it is evident from the results of the Pearson Correlation X and Y analysis that has a value of .134 . However, several dimensions of the Marketing Mix have a relationship with Customer Loyalty, because several dimensions have a sig value. below 0.05 consists of dimensions of product, place, person and physical evidence, which are individually proven value for Customer Loyalty at the DetailBOX Autodetailing Center Company.